PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERN PEMERINTAH DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KEUANGAN PEMERINTAH KOTA BANDA ACEH - Muhammad Ichlas, Hasan Basri, Muhammad Arfan. (Jurnal Akuntansi, 2014)
Abstract: This study aims to; (1) examine the effect of the implementation of the Government Accounting Standards, Government Internal Control System, and the accessibility of the financial statements together towards financial accountability Government of Banda Aceh. (2) examine the implementation of Governmental Accounting Standards for financial accountability of the Government of Banda Aceh. (3) examine the application of the Internal Control System of financial accountability of the government to the Government of Banda Aceh. (4) examine the accessibility of the financial statements for the financial accountability of the Government of Banda Aceh. The object of this research is all the institutions / agencies in the Government of Banda Aceh. Source of data used in this study include primary data and secondary data. While research data collection techniques done with documentation techniques. The analytical method used is Multiple Linear Regression Analysis. The results showed that; (1) the application of the Government Accounting Standards, Internal Control System of the Government, and financial accessibility jointly influence the financial accountability of the Government of Banda Aceh. (2) the implementation of Governmental Accounting Standards influence the financial accountability of the Government of Banda Aceh. (3) the application of the Internal Control System Government influence on the Government's financial accountability of Banda Aceh. (4) accessibility of financial statements affect the financial accountability of the Government of Banda Aceh.Keyword: Government Accounting Standards, Government Internal Control System, Accessibility of Financial Statements, Financial Accountability Government.Abstrak: Penelitian ini bertujuan untuk; (1) menguji pengaruh penerapan Standar Akuntansi Pemerintahan, Sistem Pengendalian Intern Pemerintah, dan aksesibilitas laporan keuangan secara bersama-sama terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (2) menguji penerapan Standar Akuntansi Pemerintahan terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (3) menguji penerapan Sistem Pengendalian Intern Pemerintah terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (4) menguji aksesibilitas laporan keuangan terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. Objek penelitian ini adalah seluruh instansi/lembaga di lingkungan Pemerintah Kota Banda Aceh. Sumber data yang digunakan dalam penelitian ini meliputi data primer dan data sekunder. Sedangkan teknik pengumpulan data penelitian dilakukan dengan teknik dokumentasi. Metode analisis yang digunakan yaitu Analisis Regresi Linear Berganda. Hasil penelitian menunjukkan bahwa; (1) penerapan Standar Akuntansi Pemerintahan, Sistem Pengendalian Intern Pemerintah, dan aksesibilitas keuangan secara bersama-sama berpengaruh terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (2) penerapan Standar Akuntansi Pemerintahan berpengaruh terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (3) penerapan Sistem Pengendalian Intern Pemerintah berpengaruh terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh. (4) Aksesibilitas laporan keuangan berpengaruh terhadap akuntabilitas keuangan Pemerintah Kota Banda Aceh.Kata kunci: Standar Akuntansi Pemerintahan, Sistem Pengendalian Intern Pemerintah, Aksesibilitas Laporan Keuangan, Akuntabilitas Keuangan Pemerintah.